Power, fatigue, and recovery changes in National Collegiate Athletic Association Division I hockey players across a competitive season - Laurent, C. M.; Fullenkamp, A. M.; Morgan, A. L.; Fischer, D. A. (The Journal of Strength and Conditioning Research, 2014)
This study aimed to evaluate changes in pre- to postseason power output, fatigue, and recovery during a repeated sprint test. Twenty National Collegiate Athletic Association Division I men's hockey athletes performed identical sessions of repeated sprint work pre- and postseason. The repeated sprint test consisted of 5 sets of 45 seconds of repeated sprint work with 90 seconds of rest in between each series of sprints. Power output (W), decrement, and recovery scores (RECs) were determined using raw data from a nonmotorized treadmill. Ratings of perceived exertion were recorded after, and perceived readiness (PR) recorded before, each series of sprints. Mean power was significantly higher in preseason vs. postseason performance during sprint 1 (760.6 vs. 691.3 W; p = 0.03), sprint 2 (719.9 vs 657.0 W; p = 0.05), sprint 4 (648.4 vs 588.9 W; p = 0.04), and sprint 5 (656.6 vs. 586.8 W, p = 0.04). Ratings of perceived exertion were significantly higher during sprints 3, 4, and 5 postseason with PR significantly higher (indicating less readiness) before sprints 3 and 4. There were no significant differences in REC or decrement score. Overall, athletes were unable to maintain power during subsequent repeated sprint work during postseason. The degree to which the athletes fatigued and recovered between sprints did not change between pre- and postseason testing, however, athletes exhibit increased perceptual strain during the repeated sprint work. These data indicate meaningful performance and perceptual differences throughout the competitive season in collegiate-level hockey players.